2019
DOI: 10.3390/md17030152
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fucoxanthin on Ultraviolet B-Induced Corneal Denervation and Inflammatory Pain in a Rat Model

Abstract: Fucoxanthin is a carotenoid with many pharmaceutical properties that is found in brown seaweed. However, the effects of fucoxanthin on corneal innervation and intense eye pain have not been extensively examined. To clarify the protective roles and underlying mechanisms of fucoxanthin on ocular lesions, we investigated the beneficial effects and mechanisms by which fucoxanthin ameliorates ultraviolet B (UVB)-induced corneal denervation and trigeminal pain. Treatment with fucoxanthin enhanced the expression of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The levels of inflammatory markers such as IL-1β, TNF-α, iNOS, and COX-2 were downregulated in an obese mouse model [138]. The protective effect of fucoxanthin was further described in UV-induced inflammation in cellular [139] and animal [140] models. Fx has also been reported exhibit anti-hypertensive properties.…”
Section: Other Activitiesmentioning
confidence: 90%
“…The levels of inflammatory markers such as IL-1β, TNF-α, iNOS, and COX-2 were downregulated in an obese mouse model [138]. The protective effect of fucoxanthin was further described in UV-induced inflammation in cellular [139] and animal [140] models. Fx has also been reported exhibit anti-hypertensive properties.…”
Section: Other Activitiesmentioning
confidence: 90%
“…It has recently been shown that fucoxanthin exhibits a lot of biological properties, including a protective activity against oxidative stress. It was presented that fucoxanthin prevents the cytotoxic effect of the oxidative agent in a dose-dependent manner and had a protective effect against UV-B radiation and DNA damaging factors [10,16,17,18,19]. This compound additionally affected the lipid metabolism and possesses anti-obesity and anti-diabetic activities [11,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of fucoxanthin have been reported to have antioxidant, anti-inflammatory, anticancer and antimicrobial effects in various tissues and cells, as tested by in vitro or in vivo experiments [ 25 , 26 , 27 , 28 ]. We demonstrated that pretreatment with fucoxanthin inhibited the ultraviolet B-induced corneal inflammatory pain and thinning of the corneal epithelial layer [ 29 , 30 ]. Due to the necessary functions that keep photoreceptors healthy, the RPE is critical for maintaining eye vision; however, the effects of fucoxanthin have not been extensively examined on oxidative stress-induced AMD and premature senescence.…”
Section: Introductionmentioning
confidence: 99%